Analisis Kendala Dalam Implementasi Kebijakan Program Kartu Tani di Desa Passo Kecamatan Teluk Ambon Baguala Kota Ambon - Pellu, Nurhaya; Damanik, Inta P N; Luhukay, Johanna M (Jurnal Agrosilvopasture-Tech, 2023)
The purpose of this study is to find out the obstacles in the implementation of the farmer card program policy, and to find solutions to the obstacles in the implementation of the farmer card program policy. The research was conducted in Paso Village, Teluk Ambon Baguala District, Ambon City. The population of this study is farmers who are members of farmer groups. The data analysis method used is descriptive kualitative using simple tabulation analysis. The results showed that farmers generally do not use farmer cards to transact at retailer kiosks. The obstacle to the realization of the Ambon City farmer card program is the absence of synchronization between stakeholders, namely from farmers, retailers, distributors, producers, provincial and city technical offices, and banks so that the farmer card program entered in Ambon City from 2017 until now has not been realized.